Utilization of Stabilizer Technology in Lights for Motorcycle - Rahmatullah Rizki; Muhamad Marsa Althaf Sawali; Dwi Irfansyah (Universitas Komputer Indonesia, 2023)
The purpose of this research is to design a tool to solve a problem where motorcyclists are often distracted by other motorcyclists' lights that go directly to the face/eyes so, that it can result in disruption of visibility at night which is not uncommon to cause accidents. The usual stabilizer consists of 2 servos that are used to move objects vertically and horizontally which are used to stabilize the movement of objects or to direct objects to the desired position such as an optical stabilizer on a cellphone camera or like a CCTV camera that can adjust the direction of the camera's view, stabilizer can also be applied to LED lights or flashlights that are used to direct the lights to the desired position, so if the tool is applied to motorcycle spotlights it can prevent the lights from pointing to the faces of other riders by adjusting the position of the spotlights. The method used in this research is an experimental research method where we will test this stabilizer in several road conditions such as inclines, derivatives, turns, and so on. After that we will compare the results of applying stabilizer technology to motorcycle lights and without using a stabilizer, whether using a stabilizer will reduce the impact of spotlights that directly hit the face/eyes which can interfere with vision or not. The results show that the application of a stabilizer on a motorcycle can reduce the impact of spotlights that directly hit the face/eyes. This is because the stabilizer can adjust the tilt angle of the lamp automatically so that the lamp lighting remains facing the road. So, it can be concluded that the stabilizer on the motorcycle lights can reduce the impact of spotlights that directly hit the face/eyes resulting in impaired vision of other motorists. This research is expected to create a useful tool for motorcyclists to prevent unwanted things from happening.